Performance Evaluation of Digital Transformation for Textile and Garment Enterprises (Journal of Fiber Bioengineering and Informatics, 2024)
Based on the balanced scorecard, starting from the IT strategic goal of digital transformation, thispaper deconstructs the strategic goal into four dimensions: “finance”, “customer”, “internal process”,and “learning and growth”. According to the characteristics of textile and garment enterprises, thispaper puts forward the performance evaluation index system for the digital transformation of textileand garment enterprises. Using this evaluation index system, we collected data from 201 textile andgarment enterprises by questionnaire and evaluated their digital transformation performance. The resultsshow that all effective sample enterprises have performed well on the first-level performance indicatorsof digital transformation. However, variance analysis shows a significant difference after grouping thesamples by size. Large enterprises are relatively best, followed by medium-sized enterprises, and smallenterprises rank third. Because the small enterprises have relatively weak performance in terms of“internal processes”, “learning, and growth” dimensions. In addition, the analysis of variance alsofound that the more developed the economy in the region where the enterprise is located, the betterits performance in the “customer” dimension. In terms of evaluating the second-level performanceindicators for all effective sample enterprises, the performance of the “internal process”, “customer”,and “learning and growth” dimensions is good. However, the performance of the “financial” dimensionis poor, with the highest performance weight. Textile and garment enterprises should fully play therole of digital transformation in the “financial” dimension. From the evaluation results of the third-level performance indicators for all effective sample enterprises, “expansion of products or services”,“reduced number of customer complaints”, and “the frequency of enterprise business and violation riskis reduced” have higher weights. Still, the ranking of performance evaluation values is lower. Thesethird-level performance indicators are specific indicators that textile and garment enterprises shouldfocus on and actively improve in digital transformation.
Keywords: Digital Transformation; Performance Evaluation; Balanced Score Card; Textile and Garment Enterprises.